Pengembangan “MICAYU”: Media Microsite untuk Proyek Prototype Free Energy Panel Surya dalam Pembelajaran Fisika Berbasis Proyek - Hidayah, Ifa; Asyhary, Fathya Zahra; Ilhamit Tamam, Ahmad Kevin (Balai Diklat Keagamaan Surabaya, 2024)
Digital-based learning media is currently very popular with education practitioners. Apart from being a trend in the world of education, digital media is able to raise the enthusiasm of students to continue to be creative and innovate in presenting learning outcomes. In the independent curriculum, learning is expected to implement student-centered active learning models, one of which is project-based learning. The aim of this research is to describe the creation of project-based physics learning media with